التأصيل الإسلامي للمنهجية اليابانية للتحسين المستمر "الكايزن" - الجهني، أحمد بن عطا الله حمدان (جامعة الإمام محمد بن سعود الإسلامية, 2023)
هدفت الدراسة إلى التعرف على الخلفية النظرية للمنهجية اليابانية للتحسين المستمر (الكايزن) والمبادئ الأساسية الحاكمة لها وصولا إلى التأصيل الإسلامي لتلك المبادئ. ولتحقيق ذلك استخدم الباحث المنهج الوصفي التحليلي، وقد خلصت الدراسة إلى أن للإسلام قصب السبق في التطبيق السليم لمبادئ منهجية الكايزن، فهي منهجية إسلامية قبل كونها يابانية. وقد اتفقت منهجية الكايزن مع الإدارة الإسلامية في مبادئ: التحسين المستمر لكل ما في المنظمة ومن الكل، والتدرج مطلب في عملية التحسين والتطوير، وتقليل الفاقد، والتركيز على مواقع العمل الفعلية، ورضا المستفيد، وضع المعايير والالتزام بها، والعمل الجماعي والمشاركة في اتخاذ القرارات، وأخيرا تبين من خلال الدراسة أن أغلب المبادئ الحاكمة لمنهجية الكايزن معان حقيقية انطبقت عليها شروط الاستنباط للمقاصد من ثبوت، وظهور، وانضباط، واطراد. The study aimed to identify the theoretical background of Kaizen and the basic principles governing it, leading to the Islamic rooting of these. To achieve this, the researcher used the descriptive analytical method. The study concluded that Islam preceded the proper application of the principles of the kaizen methodology, as it was an Islamic methodology before the Japanese. The Kaizen methodology agreed with the Islamic administration in the principles of continuous improvement of everything in the organization, and from all, gradualism is a requirement in the process of improving an development, reduction of waste, focus on actual work sites, beneficiary satisfaction, setting standards and commitment to them, Teamwork, and participation in decision making, and finally, it was found through the study that most of the principles governing the Kaizen methodology are real meanings to which the conditions of the deduction for proof, emergence, discipline, and steadiness have been applied.
Keywords: التأصيل الإسلامي -- الإدارة الإسلامية -- المنهجية اليابانية -- الممارسات الإدارية -- الفكر الإداري